Pengaruh Stres Kerja Terhadap Motivasi Kerja Dengan Penerapan K3 Sebagai Variabel Moderator Pada PT. PLNT-Manokwari - Yulius Heri Saptomo; Nurwidianto Nurwidianto; Katrin Rumbiak (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
ABSTRACT The purpose of this study was to determine the direct effect of work stress on occupational safety and health, work stress on work motivation, occupational safety and health on work motivation and the indirect effect of work stress on work motivation through Occupational Safety and Health (K3) at PLNT- Manokwari. The research used in this research is quantitative. The technique of determining the sample uses a saturated sample, where all members of the population are sampled. The number of respondents who were used as samples were 51 respondents. Data collection techniques used are observation, interviews and questionnaires. The data analysis technique used is path analysis technique. The results of this study indicate that work stress has an effect on occupational health and safety (K3). Job stress is formed by research factors, role demands and interpersonal investigations. Job stress does not affect employee motivation in carrying out work. Occupational Health and Safety (K3) has a direct effect on work motivation. This shows that employees already understand occupational safety and health to avoid work accidents. Work stress affects work motivation through occupational health and safety